Pelatihan Penggunaan Algoritma Euclid Dalam Perhitungan Kpk Dan Fpb Di Sd Inpres Jaya Makmur - Syahfitriani Br Ginting; Astuti Astuti; Jumiarsih Jumiarsih; Luluk Ernawati; Fadhiila Salwa Raiihany; Warpini Warpini; Nada Febrianti Kumalasari (Institut Teknologi dan Bisnis Semarang, 2023)
To complete and determine the value of FPB and KPK many students are constrained. This happens due to the lack of understanding of students how to determine the value of the FPB and the KPK. This service focuses on training Euclid's algorithm in FPB and KPK material. This service aims to provide training to teachers on the Euclidean algorithm on FPB and KPK materials at Elementary School Jaya Makmur. This service activity was carried out with 5 material sections where in each section used the lecture method, questions and answers and discussions with teachers at SD Inpres Makmur Jaya. The results of the community service activities carried out are: 1) Increased understanding of teachers regarding determining the value of the FPB and KPK material algorithms; 2) Teachers feel happy and find new ways to solve FPB and KPK materials, especially in large numbers.